The challenges and practices of investigative journalism in the Arab world through the ARIJ podcast are the focus of this descriptive and analytical study, which draws on a sample of episodes - Azza Ikhlef, Meriem Azza Ikhlef (International Journal of Social Communication, 2025)
The present study aims to illuminate the manner in which the Arab Institute for Research and Journalism (ARIJ) utilises the podcast medium to exhibit its investigative endeavours, thereby introducing its investigative work and the prevailing conditions that facilitate such research within various Arab countries. The present study adopted a descriptive and analytical approach. The research community was represented in all episodes of ARIJ's podcast for the first and second seasons by adopting a purposive sample. It was determined that content analysis was the most appropriate tool for this study, and this approach was successful in reaching a number of results, most notably: ARIJ podcasts concentrate on the most significant challenges confronting journalists in the course of conducting investigative research in various Arab countries, in addition to humanitarian and social issues of a human rights nature in these countries